Higher Education Scholarship: Gate To Develop Educational Human Resource Quality - Aliyyah, Rusi Rusmiati; Rosyidi, Unifah; Rugaiyah, Rugaiyah (International Journal for Educational and Vocational Studies, 2019)
Bidik Misi "(BM) is an extraordinary scholarship provided by the Government of Indonesia with two criteria main: economic needs and academic performance, and added a test Islamic Education at private universities. Since its introduction in 2010, the number of candidates has increased every year, causing difficulties in choosing the most qualified candidates. This study aims to find the effectiveness of the recruitment of participants in scholarship programs for the poor and how to develop the quality of educational resources in Indonesia. Although they have requirements that are not the same as regular students in participating in the admission process at universities, this study shows that private universities can develop the quality of human resources through the BM program.